Myogenic Tone in Peripheral Resistance Arteries and Arterioles: The Pressure Is On! - Jackson, William F. (Frontiers in Physiology, 2021)
Resistance arteries and downstream arterioles in the peripheral microcirculation contribute substantially to peripheral vascular resistance, control of blood pressure, the distribution of blood flow to and within tissues, capillary pressure, and microvascular fluid exchange. A hall-mark feature of these vessels is myogenic tone. This pressure-induced, steady-state level of vascular smooth muscle activity maintains arteriolar and resistance artery internal diameter at 50-80% of their maximum passive diameter providing these vessels with the ability to dilate, reducing vascular resistance and increasing blood flow, or constrict to produce the opposite effect. Despite the central importance of resistance artery and arteriolar myogenic tone in cardiovascular physiology and pathophysiology, our understanding of signaling pathways underlying this key microvascular property remains incomplete. This brief review will present our current understanding of the multiple mechanisms that appear to underlie myogenic tone including the roles played by G-protein-coupled receptors, a variety of ion channels and several kinases that have been linked to pressure-induced, steady-state activity of vascular smooth muscle cells in the wall of resistance arteries and arterioles. Emphasis will be placed on the portions of the signaling pathways underlying myogenic tone for which there is lack of consensus in the literature and areas where our understanding is clearly incomplete.